Identificación y discriminación de los fenotipos del complejo Minquartia guianensis Aublet (coulaceae) “huacapú” en la amazonía peruana - Torres Montenegro, Luis Alberto (2023)
This study explores patterns of morphological variation in Minquartia guianensis Aubl. through morphometric analysis of six vegetative characters, with the objective of discriminating four phenotypes that were pre-established based on the type of indument. First, we explored the morphometric and morphological data using a Hierarchical Clustering Analysis (UPGMA) with k=4. Subsequently, we analyzed the six morphometric variables using Principal Components (PCA) and evaluated their relationship, to exclude the one with the highest correlation in further analyses. With the remaining five variables, we performed a Linear Discriminant Analysis (LDA) for the phenotypes and explored to discriminate by soil type and by watershed. Six groups were pre-established for both, for soil type and for watershed . A total of 176 specimens from national and international herbaria and some from field collections were studied. The Glabra and Punctata phenotypes were discriminated effectively, with a success rate of 78.98%. The width of the petiole and the number of secondary veins were the characters that contributed the most to the discrimination of the phenotypes in the first component (LD1=81.9%). The four phenotypes are significantly different (p values <0.01) and the Glabra phenotype is the most distant (R values >0.70) of the four. On the other hand, the percentage of prediction of discrimination by type of soil was 45.14%, while the prediction by watershed only reaches 37.14%. This indicates a low relationship among the specimens of M. guianensis with the type of soil and watershed and does not allow to discriminate the specimens studied.